Marketing Analysis of MORINA VILLA AND RESTAURANT in Waingapu East Sumba - Susila, I Made Gede Darma; Anggara, I Gusti Made Dwi Candra; Wulandari, Pande Putu; Swandewi, Ni Kadek; Sumadi, I Gede (Jurnal Manajemen Pelayanan Hotel, 2024)
The development of tourism in East Sumba is getting more rapid, shown by the emergence of new tourist attractions in the area. This has led to the development of several tourism business services to support the sustainability of tourism in the area by showing the development of accommodation services in Waingapu City. Morinda Villa and Resto is one of the accommodations that offers beautiful hill views. The purpose of this study is to find out the 4P marketing that has been carried out, and analyze what is needed by managers for the sustainability of tourist accommodation in Morinda Villa and Resto. The data collection technique in this study uses observation, interviews and literature studies. Then it was analyzed using a qualitative descriptive approach from data collection, data reduction to data analysis. The results of the study show that the products owned by this accommodation are diverse. In terms of location, road access to the location still needs to be improved to make it easier for tourists to reach this accommodation. In addition, in terms of price, the price given is in accordance with the experience obtained by tourists who stay. Furthermore, in terms of promotion, this activity has been carried out online and offline to prospective visitors. The next research suggestion is to create the right marketing strategy to be implemented in Morinda Villa and Resto. This is because this accommodation has its own uniqueness for tourists to choose as a place to stay, but the obstacles they have also need to be fixed to maintain the sustainability of tourists who stay.